Lane keeping performances subjected to whole-body vibrations - Azizan, Amzar; Padil, Husna (International Journal of Engineering and Technology, 2018)
Despite the fact that many research have been carried out on the characterization of the effects of whole-body vibration on seated occupantsâ€™ comfort, there is still very little scientific knowledge regarding drowsiness caused by the vibrations. Furthermore, there are less verified measurement methods available to quantify the whole body vibration-induced drowsiness of the vehicle occupants. This study is therefore set out to evaluate the effect of vibrations on drowsiness. 20 male volunteers have been recruited for this experiment. The data for this study is gathered from 10-minute simulated driving sessions under both no-vibration conditions and with a vibration that is randomly organized. Gaussian random vibration, with 1-15 Hz frequency bandwidth at 0.2 ms-2 r.m.s. for 30 minutes, is applied. During the driving session, the volunteers are required to obey the speed limit of a 100 kph and keep a consistent position in the left-hand lane. The deviation in the lateral position are recorded and analyzed. Additionally, the volunteers are also asked to rate their subjective drowsiness level by means of Karolinska Sleepiness Scale (KSS) scores for every five minutes. Based on the results, the role of vibration in promoting drowsiness can be observed from the driving impairment following 30-mins exposure to vibration.Â Â